2020
DOI: 10.21203/rs.3.rs-23325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Status of Hypothalamic-pituitary-thyroid axis and Prolactin level in Patients with First-episode of Bipolar Disorder in Mania State

Abstract: Background Bipolar disorder (BD)-mania symptoms are stimulated by disease of the thyroid. Methods This study included 70 patients diagnosed with first-episode BD-mania and 70 healthy controls (HC) matched for age and sex. We aimed to determine upstream thyroid hormone interactions on the anterior pituitary, and find differences between thyroid-stimulating-hormone (TSH) and Prolactin (PRL) in the patients with first-episode of BD-mania. There were significant changes in triiodothyronine (TT3), total thyroxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…High PRL levels in patients with SZ or BD are often attributed to APs. Nevertheless, there have been reports of high prolactin levels in drug-naive patients with SZ or other psychotic disorders ( 41 ), as well as in BD ( 42 ). The data on PRL in drug-free or drug-naïve patients are still equivocal ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High PRL levels in patients with SZ or BD are often attributed to APs. Nevertheless, there have been reports of high prolactin levels in drug-naive patients with SZ or other psychotic disorders ( 41 ), as well as in BD ( 42 ). The data on PRL in drug-free or drug-naïve patients are still equivocal ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of the studies on long-acting injectable (LAI) and second-generation oral antipsychotics reported better clinical outcomes with LAIs but higher PRL level and side effects ( 44 ). Many hypotheses have been proposed, including relationships between PRL and dopamine, links between PRL and stress, effects of the Thyroid Stimulating Hormone ( 4 ) axis on PRL, as well as pro-inflammatory and detrimental cognitive effects of PRL ( 42 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients ranged from 15.9 [40] to 53.3 [52]. The diagnostic criteria for BD included the Diagnostic and Statistical Manual of Mental Disorders (DSM) [27,29,30,33,35,38,41,43,44,[50][51][52], the International Classi cation of Diseases diagnostic Criteria, Edition10(ICD 10) [28, 31,34,36,39,40,42,48], the Chinese Criteria for Classi cation and Diagnosis of Mental Disorders, Edition3(CCCD-3) [32,37,[45][46][47]49], and the Diagnostic Criteria for Functional Psychoses (3rd) [53]. In most studies, euthyroid patients or no history of thyroid disease were required to be included, while two studies [27,30] had no any description of thyroid function.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In most studies, euthyroid patients or no history of thyroid disease were required to be included, while two studies [27,30] had no any description of thyroid function. Except for 2 studies [36, 47] that didn't mention it, and one study [35] just said it was immunoassay, methods for measuring serum TH included Electrochemiluminescence immunoassay (ECLIA) [28,31,34,[39][40][41][42]44], Chemiluminescence immunoassay (CLIA) [27,29,30,32,33,37,38,45], Radioimmunoassay (RIA) [46,[50][51][52][53], Enzyme linked immunosorbent assay (ELISA) [43,[48][49][50], Immuno uorescence (IF) [50], and most studies show that they were measured in the morning. In terms of drug expression, some studies directly speci ed medication-free [30,31,33,34,42,45], the duration of drug discontinuation in other studies were separately 6 months [27,29,36], 3 months [32, 39], 2 months [43], 1 month [37,40,46,50], and at least 2 weeks [28, 35,38,…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation